The anatomical relationship of the neurovascular structures in direct posterior lateral gastrocnemius split approach for posterolateral tibial plateau fractures - ŞİRİN, EVRİM (My University, 2018)
Purpose To evaluate the distances between the incision and neurovascular structures in direct posterior split-gastrocnemius approach for tibial plateau fractures. Methods Thirteen fresh-frozen cadavers were used in the study. The distance between the neurovascular structures medial and lateral to the incision was measured from the tibial joint line and at a level 5 cm distal to the joint line. Results The mean distance between the incision and medial neurovascular structures was 10.09 ± 3.47 mm (range 5.63–16.51 mm) at the level of the tibial joint line and 10.39 ± 2.57 mm (range 5.79–14.09 mm) at a level 5 cm distal to the joint line. The mean distance between the incision and the common peroneal nerve was 13.44 ± 4.17 mm (range 6.28–20.72 mm) at the level of the tibial joint line and 19.56 ± 5.24 mm (range 12.58–26.74 mm) at a level 5 cm distal to the joint line. Conclusions In isolated posterolateral tibial plateau fractures, it is possible to apply anatomical reduction and buttress plating on the posterior surface with a direct posterior split-gastrocnemius approach. With a thorough understanding of the regional anatomy, this approach can be safely performed by experienced orthopaedists
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; ACİL TIP; Klinik Tıp; Klinik Tıp (MED); EMERGENCY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Acil Tıp Hizmetleri; Emergency Medical Services; Tibial plateau fracture; Posterolateral; Surgical approach; FIXATION; Tibial plateau fracture; Posterolateral; Surgical approach